THE COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE BEFORE (2008-2010) AND AFTER (2012-2014) IPO (CASE STUDY: FIVE LISTED COMPANIES IN IDX) - Lengkong, Novita Maria; Tielung, Maria V. J. (FEB Universitas Sam Ratulangi Manado, 2015)
In IDX (Indonesian Stock Exchange) there are some stock listed. The listed company in IDX means that the company is published their prospectus and fund fact share to public, or it called Go Public Company. The purpose of the research is to analyze the significant financial performance before and after IPO. These are as variables on this research. The type of analysis used is dependent Normality Test and paired sample T-Test which enables the researcher to compare the financial performance before and after IPO. The finding there is significant difference between before and after IPO on five listed companies in IDX, it is calculated by T-Count and T-Table. The T-Count ROA is 3.116 is bigger than T-Table, T-Count ROE is 2.648 is bigger than T-Table, T-Count Profit Margin is 2.182 is bigger than T-Table, means that the different is significant between before and after IPO. The company better to maintain and to improve its financial performance due to management's decision to go public is the first step to give the company's financial progress. Keywords: comparative analysis, financial performance, listed companies